Augusto Boal: alguns encontros e desencontros com Bertolt Brecht - Silva, Anderson de Souza Zanetti da [UNESP] (2015)
The objective of this research is to discuss some aspects of the theatrical context of Augusto Boal, whose aesthetic-political paradigm is the poetics of Bertolt Brecht. With this procedure, some agreements and disagreements of Boal's poetic are identified with certain prospects of Brecht. In order to fully understand it, the following division is carried out: 1) some historical agreements and disagreements; 2) some political agreements and disagreements; 3) some aesthetic agreements and disagreements. This procedure only serves as a thematic organization, not changing the importance of discussing, in a correlated way, the historical, political and aesthetic production of Augusto Boal. While considering certain hypotheses, many crossover points arise and help to understand not only the theater of Boal, but also the significance that his work has for the history of Brazilian theater. In this context, it is not possible to deal with the left-wing theater in Brazil without addressing the arrival of Brecht's work in the country. As a result, there is an assumption that understanding the importance of Augusto Boal theater means understanding how Brecht's work serves as a model for the development of Brazilian poetic.